The paradigm of copyright development in the United States of America - Yuzvyk, Iryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2024)
This article focuses on the paradigm of copyright law development in the United States of America, with a particular emphasis on the various theoretical rationales and influences that have shaped its development. The emphasis is placed on the utilitarian nature of the American approach to copyright, which reflects the desire to maximize overall utility and economic rights, as opposed to European traditions that focus on the author’s non-property rights. The article analyzes the main philosophical foundations on which US intellectual property law is based, including Bentham’s utilitarianism, Locke’s theory of the wasteland of labor, and Hegel’s theory of personal rights. Particular attention is paid to the analysis of the absence of the concept of non-property rights in American law, which has long been an obstacle to the US accession to the Berne Convention for the Protection of Literary and Artistic Works. Despite ratifying this Convention in 1989, the United States has avoided implementing the provisions on moral rights, believing that current legislation sufficiently meets the requirements of the Convention. The article provides a theoretical analysis of the criticism of this position by both American and Ukrainian scholars. The author characterizes the impact of the Berne Convention on American copyright law, emphasizing the difficulties associated with the implementation of moral rights. The article highlights the main provisions of the Copyright Act of 1976, in particular, the requirements for the originality of works, the criteria for their fixation in a tangible form and the list of categories subject to protection. The article emphasizes that although copyright protection is focused on the economic remuneration of creators, it also contributes to the common good by enriching the cultural context.